2019
DOI: 10.1038/s12276-019-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral ureteral obstruction causes gut microbial dysbiosis and metabolome disorders contributing to tubulointerstitial fibrosis

Abstract: Chronic kidney disease (CKD) increases the risk and prevalence of cardiovascular disease (CVD) morbidity and mortality. Recent studies have revealed marked changes in the composition of the microbiome and the metabolome and their potential influence in renal disease and CVD via the accumulation of microbial-derived uremic toxins. However, the effect of unilateral ureteral obstruction (UUO) on the gut microbiome and circulating metabolites is unknown. Male Sprague-Dawley rats were randomized to UUO and sham-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 85 publications
6
72
1
Order By: Relevance
“…Excessive uremic toxins are produced as a result of GM alteration, which are implicated in the kidney disease development. Dysbiotic GM and metabolites can contribute to tubulointerstitial fibrosis, which might be mediated by tryptophan‐derived metabolite‐induced inflammation and oxidative stress . Meanwhile, the interaction between the gut epithelia and some commensal bacteria induces the rapid generation of reactive oxygen species, which participate in the development of nonalcoholic fatty liver disease …”
Section: Discussionmentioning
confidence: 99%
“…Excessive uremic toxins are produced as a result of GM alteration, which are implicated in the kidney disease development. Dysbiotic GM and metabolites can contribute to tubulointerstitial fibrosis, which might be mediated by tryptophan‐derived metabolite‐induced inflammation and oxidative stress . Meanwhile, the interaction between the gut epithelia and some commensal bacteria induces the rapid generation of reactive oxygen species, which participate in the development of nonalcoholic fatty liver disease …”
Section: Discussionmentioning
confidence: 99%
“…Fries showed significant antitumor, diuretic, and renoprotective effects . Our recent study demonstrated that ergone inhibited NF‐κB signaling and α‐SMA expression in 5/6 nephrectomised and unilateral ureteral obstruction rats (Figure and Table ).…”
Section: Small Molecules Against Emtmentioning
confidence: 96%
“…Metabolomics (or metabonomics) belong to one of component of systems biology. Recent technological advances have enabled rapid and systematic identification of a large myriad of metabolites or compounds by using sensitive and high‐throughput metabolomic techniques . Metabolomics has the potential to facilitate an understanding and illuminating of the action mechanisms of TCM .…”
Section: Introductionmentioning
confidence: 99%
“…Recent technological advances have enabled rapid and systematic identification of a large myriad of metabolites or compounds by using sensitive and high-throughput metabolomic techniques. [19][20][21][22][23][24] Metabolomics has the potential to facilitate an understanding and illuminating of the action mechanisms of TCM. [25] Although various mass spectrometry platforms could be used for metabolomics, ultra-performance liquid chromatography coupled with high-definition mass spectrometry (UPLC-HDMS) has been considered to be more suitable for analyzing the metabolite profiling and metabolite identification due to its enhanced reproducibility of retention time.…”
Section: Introductionmentioning
confidence: 99%